The epidemiological profile of cancer in Beni Mellal: a cross-sectional descriptive study - Mohamed, Aboufaras; Karima, Selmaoui; Nadia, Ouzennou (Intelektual Pustaka Media Utama, 2024)
In Morocco, where cancer is a major public health problem, the characteristics of cancer in the Beni Mellal-Khenifra region of Morocco are unknown. Our objective was to establish the epidemiological profile of cancer in this region and the main risk factors influencing cancer. We conducted a cross-sectional study, including all types of cancer, with a sample of 100 patients at the Beni Mellal regional oncology center. Data collected in June and July 2021 using a questionnaire, pre-tested, and analyzed using SPSS and Excel. The questionnaire included sections on cancer-related clinical characteristics and other items related to cancer risk exposures. Gyneco-mammary cancers occupied the first position (49%). The most common localization of cancer in women was breast cancer, with a proportion of 63% of cases recorded during the period studied. In men, lung cancer was the most frequent location at 17%. We found some possible risk factors for cancer: tobacco and alcohol use, dietary habits, use of hormonal contraceptive methods, low income, pollution, sun radiation, exposure to asbestos, family history of cancer, and diseases associated with cancer. Women’s cancers are very common in the region. Several factors are responsible for this frequency. These results suggest several avenues for further research.